Experimental study on drying kinetics of anchovy using centrifugal fluidized bed technique - Dongbang, Watcharin; Pirompugd, Worachest (International Journal of Agricultural and Biological Engineering, 2015)
The present study investigated the drying kinetics of anchovy experimentally using centrifugal fluidized bed technique. The main purpose was to experimentally investigate the effect of the inlet air temperature on the drying kinetics of anchovy in a centrifugal fluidized bed dryer, to fit the experimental data to the widely used mathematical models of drying. Further, the effective moisture diffusivity and activation energy in anchovy drying were investigated in the current work. The drying experiment was conducted at drying air temperatures ranging over 70-120°C. The air velocity and rotating speed of the air-distributor were fixed at 1.5 m/s and 150 r/min, respectively. Pressure drop across bed was approximately 390 Pa, while the layer height was fixed at approximately 2 cm. The anchovies were dried starting from 412% db down to 16% db; drying time ranged from 64 min to 172 min. It was found that the drying temperature was a significant factor in decreasing the moisture content, moisture diffusivity and drying time. The moisture diffusivity and activation energy were investigated at 0.11×10-9-0.25 ×10-9 m2/s and 20.32 kJ/mol, respectively. When compared to existing models, the Midilli model proved to be in good agreement with change in moisture ratio.Keywords: centrifugal fluidized bed, drying kinetics, anchovy, moisture diffusivity, activation energyDOI: 10.3965/j.ijabe.20150805.1975Citation: Dongbang W, Pirompugd W. Experimental study on drying kinetics of anchovy using centrifugal fluidized bed technique. Int J Agric & Biol Eng, 2015; 8(5): 132－141.